If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3 = 2x + 1 Reorder the terms: -3 + 10x = 2x + 1 Reorder the terms: -3 + 10x = 1 + 2x Solving -3 + 10x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 10x + -2x = 1 + 2x + -2x Combine like terms: 10x + -2x = 8x -3 + 8x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 8x = 1 + 0 -3 + 8x = 1 Add '3' to each side of the equation. -3 + 3 + 8x = 1 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = 1 + 3 8x = 1 + 3 Combine like terms: 1 + 3 = 4 8x = 4 Divide each side by '8'. x = 0.5 Simplifying x = 0.5
| sin(45)=x/18 | | x+8=x*(x-6) | | 81x^3+1=0 | | (p^-4b)/(12c^2) | | 2(3x-1)-(x-2)=5 | | (p^-4b)/12c^-2 | | 2xy-x+2y+1=0 | | 600x=8000+300x | | 600x=12000+300x | | 600x=200x+12000 | | 4x+11=38-3x | | 4x+12=20-12x | | 3x+30=45 | | (2x+4)4=8 | | -4+4x=-12x+10x | | y=-x^3+9x^2-24x+10 | | -/-18/ | | 23+4x+y=9x | | 8/?x5=10 | | x^3+2=6 | | 2x+2y=3x | | 2x=3x^4 | | 3(5x-1)-2x+4=-64 | | X^3+y^3-3xy-3=0 | | -6-4x=42 | | 3-3x+2(x-5)=7 | | x^2+(m-1)x+m-2=0 | | 8x+60=6x+160 | | 3z^2=9z | | x=21-5 | | 23x^2-42x-8=0 | | 5x^2+27x+36=0 |